Heidegger: a linguagem poética como superação da metafísica - Barbosa, Alexandre Guedes (2023)
In the spread of his self-titled “path of thought”, Martin Heidegger framed metaphysics from the ontological difference, a theme that deals with the difference between Being and being, which allows him to affirm that metaphysics neither thinks nor represents Being by itself, but as entity (being of beings). Thus, since for Heidegger the History of Western Thought is a reflection of the way in which metaphysics treats ontology, he sees the need to understand Being properly, then, launches the project of overcoming metaphysics. Given the different interpretations on that subject, ranging from the allegation of a failure to a visualization of a possible transformation of the initial project, the guiding objective of this work is to identify the establishment of this overcoming based on what we believe to be two essential goals of the project: 1) the reach of understanding of Being by itself; 2) the establishment of a language appropriate to this understanding. We will see that the poetic language, for being the free manifestation of time as imagetic prefiguration, intuitive element of the inaugural and creator naming of arising presence, gathering the above goals, allows us to identify that, with the effectiveness of metaphysics’ overcoming (Überwindung), there is a transposition to the unthinking and unsaid by it, which is only possible by abandoning it (Überlassen). However, in this abandonment, it will be possible to understand that metaphysics is not rejected, but transformed in its essence by Being’s thought.